2016
DOI: 10.1021/acs.jpclett.6b02613
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Strong-Field Effects in Indirect Photofragmentation Reactions

Abstract: Exploring molecular breakup processes induced by light-matter interactions has both fundamental and practical implications. However, it remains a challenge to elucidate the underlying reaction mechanism in the strong field regime, where the potentials of the reactant are modified dramatically. Here we perform a theoretical analysis combined with a time-dependent wavepacket calculation to show how a strong ultrafast laser field affects the photofragment products. As an example, we examine the photochemical reac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…Numerous theoretical and experimental studies have confirmed that LICIs have noticeable impact on different dynamical properties (like molecular alignment, photodissociation probability, etc...). [14][15][16][17][18][19] Furthermore, a strong effect in the angular distribution of the photofragments has been revealed that serves as a direct signature of the LICI. 18 The first experimental observation of LICIs in diatomic molecules was made by Bucksbaum et al.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous theoretical and experimental studies have confirmed that LICIs have noticeable impact on different dynamical properties (like molecular alignment, photodissociation probability, etc...). [14][15][16][17][18][19] Furthermore, a strong effect in the angular distribution of the photofragments has been revealed that serves as a direct signature of the LICI. 18 The first experimental observation of LICIs in diatomic molecules was made by Bucksbaum et al.…”
Section: Introductionmentioning
confidence: 99%
“…Since the computational complexity of quantum system identification algorithm usually exponentially increases with the number of qubits, it is expected to develop more efficient identification algorithms for quantum parameter identification. Other new directions for future research include the mechanism identification of physical process [38] and the identification of quantum networks [39], [40] where the network topology could be taken advantaged of.…”
Section: Discussionmentioning
confidence: 99%
“…For Example 1,(14) is already in the Kalman canonical form and the minimal subsystem isẋ 1 = θ 1 x 1 + u, y = x 1 . Hence, θ 1 is identifiable and θ 2 is unidentifiable.…”
Section: B Non-minimal Systemsmentioning
confidence: 99%